2010
DOI: 10.1902/jop.2010.100080
|View full text |Cite
|
Sign up to set email alerts
|

Oral Malodorous Compound Causes Oxidative Stress and p53‐Mediated Programmed Cell Death in Keratinocyte Stem Cells

Abstract: We conclude that H(2)S can induce apoptosis in human keratinocyte stem cells, a key component of the epithelial barrier, following DNA damage and p53 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 27 publications
2
51
0
1
Order By: Relevance
“…In a previous study, Tonetti et al have implicated that inflammatory stimuli induced DNA fragmentation and upregulation of p53 protein expression in gingival tissues [17]. Calenic et al have shown that after H 2 S incubation p53 levels have been elevated and accompanied with an increase of apoptotic keratinocyte stem cells [18]. Our data support these findings as we found increased p53 immunoreactivity in tissue sections of patients with periodontitis compared to gingivitis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a previous study, Tonetti et al have implicated that inflammatory stimuli induced DNA fragmentation and upregulation of p53 protein expression in gingival tissues [17]. Calenic et al have shown that after H 2 S incubation p53 levels have been elevated and accompanied with an increase of apoptotic keratinocyte stem cells [18]. Our data support these findings as we found increased p53 immunoreactivity in tissue sections of patients with periodontitis compared to gingivitis.…”
Section: Discussionsupporting
confidence: 90%
“…Different studies have demonstrated that stimulation with disease-associated fibronectin fragments induces p53 expression changes in periodontal ligament fibroblasts [15,16]. These studies have underlined the importance of p53 in the pathogenesis of periodontal diseases indicating that p53-induced apoptotic processes play a role in oral inflammatory pathologies [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated intracellular levels of ROS can ultimately lead to DNA damage. Increased levels of ROS associated with DNA damage were also detected in normal keratinocytes [105] and keratinocyte stem cells [106]. In addition, 24 or 48 h of incubation with physiological concentrations of VSCs (specifically H 2 S) can induce apoptosis in different oral cellular types.…”
Section: Ppmmentioning
confidence: 94%
“…Human skin cell line Apoptosis -mitochondrial pathway activated; DNA damage; p53 and Bax activity increased [106] Oral epithelia Keratinocyte stem cells…”
Section: Fetor Hepaticusmentioning
confidence: 99%
“…Table 3: Biological effects of low physiological concentrations of H2S on different oral cell types (1ng/ml H2S) [7]. Thus reports show that H 2 S is directly linked to the initiation and development of periodontal diseases: the compound inhibits the proliferation process of oral keratinocyte cells [6], decreases protein synthesis in oral fibroblasts, and inhibits collagen synthesis or basal membrane synthesis [7]. There seem to be a direct relation between the type of the biological effect induced by H 2 S and the H 2 S levels.…”
Section: Environmental Analytical Chemistrymentioning
confidence: 99%